Impliquer le secteur de la santé dans la prévention et la prise en charge des mutilations génitales féminines: résultats d'une recherche formative en Guinée - Mamadou Dioulde Balde; Anne Marie Soumah; Aissatou Diallo; Alpha Oumar Sall; Vernon Mochache; Wisal Ahmed; Amadou Oury Toure; Ramata Diallo; Sadan Camara; Sarah O'Neill; Christina C. Pallitto (BMC, 2022)
Plain language summary Despite the implementation of various interventions to prevent female genital mutilation (FGM), it is still widely practiced in Guinea, and health care providers are increasingly being implicated in the practice. We conducted research in three regions of Guinea, namely, Faranah, Labe and Conakry, to understand factors that might be addressed to strengthen the role of the health sector in prevention and care of women and girls who have undergone FGM. Our findings highlight the need to strengthen the capacity of health care providers to be able to identify cases of FGM and manage complications. The study also highlights the importance of engaging health care providers in efforts to prevent FGM, which will require that any trainings include an opportunity to discuss their own values and beliefs around FGM so that they are better equipped to communicate with their clients and patients in a sensitive and non-judgmental manner, whether during consultation visits or community health outreach activities. The results of this research have informed the development of a health system strengthening intervention package for the prevention and care of FGM, which is being tested in Kenya, Somalia, and Guinea.